Cystic adenomatoid malformation of the lung: A diagnostic dilemma - Mohta Anup; Kanojia Ravi; Bathla Sapna; Khurana Nita (Wolters Kluwer Medknow Publications, 2009)
Congenital cystic adenomatoid malformation (CCAM) of the lung is an uncommon anomaly that arises from excessive disorganised proliferation of tubular bronchial structures excluding the alveoli. These are believed to represent focal pulmonary dysplasia because skeletal muscle may be identified from within the cyst wall. This report describes a case of an infant operated for presumed diagnosis of congenital diaphragmatic hernia. Diaphragm was found to be normal and further investigations revealed cystic mass in the lower lobe of the left lung. Thoracotomy was done to resect the lesion that revealed a type II CCAM on histopathological examination. The case stresses the need for better clinical examination and advanced radiological investigations in doubtful cases.